Climate and coastal low-cloud dynamic in the hyperarid Atacama fog Desert and the geographic distribution of Tillandsia landbeckii (Bromeliaceae) dune ecosystems - García, Juan-Luis; Lobos-Roco, Felipe; Schween, Jan H.; del Río, Camilo; Osses, Pablo; Vives, Raimundo; Pezoa, Mariana; Siegmund, Alexander; Latorre, Claudio; Alfaro, Fernando; Koch, Marcus; Loehnert, Ulrich (Plant systematics and evolution, 2021)
Despite the extensive area covered by the coastal Atacama fog Desert (18-32° S), there is a lack of understanding of its most notorious characteristics, including fog water potential, frequency of fog presence, spatial fog gradients or fog effect in ecosystems, such as Tillandsia fields. Here we discuss new meteorological data for the foggiest season (July-August-September, JAS) in 2018 and 2019. Our meteorological stations lie between 750 and 1211 m a. s. l. at two sites within the Cordillera de la Costa in the hyperarid Atacama (20° S): Cerro Oyarbide and Alto Patache. The data show steep spatial gradients together with rapid changes in the low atmosphere linked to the advection of contrasting coastal (humid and cold) and continental (dry and warm) air masses. One main implication is that fog presence and fog water yields tend to be negatively related to both distance to the coast and elevation. Strong afternoon SW winds advect moisture inland, which take the form of fog in only about 6% of the JAS at 1211 m a. s. l., but 65% at 750 m a. s. l. on the coastal cliff. Although sporadic, long lasting fog events embrace well-mixed marine boundary layer conditions and thick fog cloud between 750 and 1211 m a. s. l. These fog events are thought to be the main source of water for the Tillandsia ecosystems and relate their geographic distribution to the lowest fog water yields recorded. Future climate trends may leave fog-dependent Tillandsia even less exposed to the already infrequent fog resulting in rapid vegetation decline.